Effects of upwelling and submarine groundwater discharges on phytoplankton communities off the north coast of the Yucatan peninsula - Becerra-Reynoso, Román; Mariño-Tapia, Ismael; Herrera-Silveira, Jorge; Enriquez, Cecilia (Frontiers in Marine Science, 2025)
IntroductionCoastal regions around the world are influenced by numerous dynamical processes that supply nutrients for primary producers and trigger the food web. Rivers, submarine groundwater discharges (SGD), sediment suspension events, and upwelling, are amongst the more important. However, it is not just the concentration, but also the composition of nutrient supply that determines the type of phytoplankton community that develops, subsequently influencing the entire food web. It is therefore necessary to better understand the link between physical processes, nutrient composition and phytoplankton response in coastal oceans. This study investigates the effects of upwelling and submarine groundwater discharges on the phytoplankton community of a wide and shallow continental shelf.MethodsResults are achieved by using numerical modeling of dispersion events, as well as field data obtained from three oceanographic cruises, each representing a different hydrographic scenario (“No upwelling”, “Minor upwelling and SGD” and “Major upwelling and minor SGD”).ResultsThe upwelled water mass (SUW – Subtropical Underwater) was primarily found at the eastern end of the shelf (Cabo Catoche), where it rises and is transported westward by advection. The oceanographic stations influenced by the upwelled water showed an increase in diatom species population, known to thrive in environments with abundant inorganic nutrients. In contrast, submarine groundwater discharges were recorded nearshore on the western half of the shelf, mainly related to karst features of hydrogeological importance (a sinkhole ring associated with the Chicxulub crater). The stations with SGD influence had higher presence of nutrients such as NH4, suggesting recycling processes. This can modify either the phytoplankton community advected from Cabo Catoche, or promote local growth, leading to a dominance of dinoflagellates and unknown flagellates.DiscussionThis result implies a food web, similar to that of the mixoplankton-dominated microbial loop, which would be fed by organic matter of continental origin.